MODAL TESTING STUDY ON BOAT-TYPE PADDY TRACTOR HULL - ZHANG Lu; CHEN Yuan; ZHOU MingGang; LIU MingYong (Jixie qiangdu)
Multi-excitation modal analysis was used to test the dynamics characteristic parameters of the boat-type paddy tractor hull after analyzing the damage of the boat-type paddy tractor shaft and bearing during the commissioning. According to the basic principle and method,the H1 modal was used to estimate the frequency response function,modal parameters were identified by the method of frequency domain poly-reference modal parameter identification,and the top 7 ranks of natural frequencies within 100 Hz and the top 3 ranks of vibration mode were obtained. The results show the lower first order natural frequency characteristic of the boat-type paddy tractor hull,and severe resonance would occur in the process of engine starting because the rotation frequency of the transmission and the vibration frequency of engine are closer to the first and second order natural modal frequencies. The analysis shows the direction to solve the problem of the intermediate shaft’s damage,and provide the basis theoretical for the design optimization of hull and structure.